Effect of irrigation on the yield and scab infection of potato (Bangladesh Journal of Agricultural Research, 2010)
An experiment was conducted in Jamalpur during the Rabi seasons of 2004-2005 and 2005-2006 to investigate the yield and scab infection of potato variety Diamant under different irrigation frequencies and quantities. Three irrigation intervals, 7, 12 and 17 days along with three levels of water quantities equaling 50, 100 and 150% of depleted soil moisture were tested for yield and scab infection of potato tubers. It was observed in 2004-2005 that irrigation interval of 12 days and watering at 100% depletion of soil moisture produced the highest fresh and total yields of 24.64 t/ha and 27.56 t/ha, respectively, whereas irrigation interval of 7 days and watering at 150% of depleted soil moisture produced the lowest fresh and total yields (21.68 t/ha and 25.98 t/ha, respectively). In 2005-2006, irrigation interval of 12 days and watering at 100% depletion of soil moisture produced the fresh and total yields of 26.27 t/ha and 27.41 t/ha, respectively, and were not found statistically different from those obtained under water application of 150% depleted soil moisture and irrigation interval of 12 days. The scab infected tubers were found the highest 4.30 t/ha in 2004-2005 and 2.97 t/ha in 2005-2006 for water application of 150% depleted soil moisture and 7 days irrigation intervals. This indicates that scab disease is more susceptible to frequent and over irrigation. Key Words: Irrigation interval; moisture depletion; scab disease.  DOI: 10.3329/bjar.v34i4.5843Bangladesh J. Agril. Res. 34(4) : 683-692, December 2009